Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 2 – Inventaire des services de santé disponibles en français et identification des déficits de services - de Moissac, Danielle; Ba, Halimatou; Gagné, Maryanne; Éthier, Sophie (Conseil communauté en santé du Manitoba, 2012)
Au Manitoba, des services de santé en français sont disponibles à Winnipeg, et plus précisément à Saint-Boniface et à Saint-Vital, où habite une forte concentration de francophones. L’objectif de ce deuxième volet de recherche sur l’accès des personnes âgées aux services de santé en français est de dresser un inventaire représentatif des services de santé publics, privés à but lucratif, privés à but non lucratif ou communautaires disponibles en français dans ces deux quartiers, pour ensuite identifier les déficits de services. On définit ici la disponibilité comme étant un service dont peuvent disposer les aînés et qui peut être utilisé par quiconque en fait la demande. Cet inventaire permettra de mieux connaître le nombre, le type et la nature des services existants et de déterminer si tous les services de santé et services sociaux disponibles en français sont répertoriés, soit dans l’Annuaire des services en français de la Société franco-manitobaine. Ceci est important, car une plus grande visibilité des services disponibles en français contribue grandement à leur utilisation par les aînés francophones et leurs aidants lorsque le besoin survient. De plus, l’inventaire permettra d’identifier le type et la nature des services manquants auxquels la population vieillissante pourrait avoir recours.

Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Trousse d’outils sur les services en français French Language Services Toolkit - Dumont, Marthe; Doucet-Simard, Suzy (2013)

Repérage de quelques obstacles linguistiques et culturels des soins de santé pour les immigrants francophones de la Nouvelle-Écosse - Fontaine, Louise (Port Acadie, 2010)
Ce texte s’attarde au concept d’« immigrant francophone » appliqué au contexte de la Nouvelle-Écosse. Contrairement à ce qu’on peut imaginer à un premier niveau d’analyse, ce concept est polysémique et le sens qu’on y attribue varie selon les acteurs sociaux qui l’utilisent. Donc, afin de mieux délimiter l’objet de notre propos, nous avançons quelques éléments de définition à prendre en compte. Il s’agit d’une recherche exploratoire orientée vers la formulation de quelques pistes de réflexion, voire quelques hypothèses de travail à vérifier lors de la réalisation de futures recherches dans le domaine de la santé auprès des communautés francophones et acadiennes de la Nouvelle-Écosse. Pour étoffer notre propos, nous présentons quelques données empiriques recueillies à même le travail de terrain mené principalement dans le milieu associatif à Halifax et dans le sud-ouest de la province depuis 2003. Dans ce contexte, nous avons mené des enquêtes en procédant notamment à de l’observation participante. Nous avons aussi eu recours à des documents écrits tels que des documents gouvernementaux, des articles dans des revues spécialisées, des journaux. Les liens que nous avons établis entre des thèmes comme langue, culture et santé nous ont conduite finalement à proposer quelques questions de recherche et quelques hypothèses de travail.

Évaluation des besoins des francophones et des Acadiens de la région de Saint-Jean pour un service de navigation - Forest, Mariève (Réseau santé en français de Terre-Neuve-et-Labrador, 2019)

Needs Assessment for a Navigation System to Serve Francophones and Acadians in the St. John’s, Newfoundland and Labrador, Area - Forest, Mariève (Sociopol for the Réseau Santé en français de Terre-Neuve-et-Labrador, 2019)
pages: 61

The pathway to diagnosis of dementia for Francophones living in a minority situation - Garcia, Linda J.; McCLeary, L.ynn; Emerson, Victor; Léopoldoff, Hélène; Dalziel, William; Drummond, Neil; Cohen, Carole; Koehn, Sharon; Silvius, James (The Gerontologist, 2014)
Purpose of the Study: As the prevalence of dementia increases, the pressure to make early diagnoses also increases. Although patients must be able to identify the symptoms to access appropriate services, they may not be equally accessible to all citizens in a multicultural society. Health care professionals and patients may lack a common “first language.” This study explores the experience of francophone persons with dementia (PWD) and their caregivers during the peri-diagnostic period. Design and Methods: Individual interviews were undertaken to elicit information regarding symptoms, the role of the family and friends, and the access to formal services. Seven PWD and their caregivers who spoke French as their primary language but who lived in a primarily English-speaking region completed the interviews. Results and Implications: No single symptom seemed sufficient to alert participants that dementia might be present. Participants communicated that there was a dire need to inform the public about the signs of dementia; they spoke of the role of the family physician and the importance of having a long-standing relationship with a health professional. For some, having similar personal characteristics, such as language and culture, might accentuate the strength of the relationship and facilitate the process of diagnosis.

Access to dementia services in a minority situation: The case of Francophones in Ontario [infographic] - Garcia, Linda; Chomienne, Marie-Hélène; Cadieux, M.-A.; Farmanova, E.; McCleary, L.; Molnar, F.; Agapitos, M.; Dalziel, W.; Khoury, L.; French-Merkley, V.; Joanisse, J. (2014)

Strategies for improved French-language health services: Perspectives of family physicians in northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Canadian Family Physician, 2015)

Le potentiel d'offre et de demande de Services médicaux et diagnostiques dans la langue de communautés minoritaires : où se situe le français en Colombie-Britannique? - Giguère, Louis; Conway, Brian (Reflets, 2014)
Une étude comparative du potentiel de services médicaux dans les langues minoritaires de Colombie-Britannique révèle que des médecins non-francophones parlant français génèrent une retombée linguistique qui amplifie l’offre potentielle de services de santé et de services sociaux en français de façon dramatique. Ce mécanisme structurant s’appliquerait aux autres professions de la santé et des services sociaux, partout au Canada et il serait plus prononcé plus le contexte est minoritaire. Les communautés francophones doivent faire plus pour identifier, engager et outiller les professionnels et professionnelles « francophiles » et elles doivent élaborer une logique d’équité innovatrice pour dégager le potentiel d’offre de services de santé et de services sociaux en français dans un contexte multilingue. Mots-clés : CFASM, CLOSM, médecins parlant français, minorités linguistiques, équité, services d’interprétation, offre et demande

Portrait des services bilingues offerts au sein des hôpitaux canadiens. Rapport - Guignard Noël, Josée; LeBlanc, J.; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Is Francophone language status associated with diffences in the health services use of rural Nova Scotians? - Langille, Donald; Rainham, Daniel; Kisely, Steve (Canadian Journal of Public Health, 2012)
L’étude a pour objet de vérifier empiriquement la validité d’un modèle théorique qui propose un système de relations liant la construction de l’identité ethnolinguistique à la satisfaction de vie, un aspect du mieux-être psychologique, et à l’autoévaluation de sa santé. Un échantillon de 8 124 élèves du secondaire, provenant de 30 conseils scolaires francophones situés à l’extérieur du Québec, a participé à l’étude. Les résultats sont conformes au modèle fondé sur la théorie de l’autodétermination, qui stipule que lorsque la construction identitaire se fait dans un contexte d’appui à des besoins psychologiques de base, elle est reliée au mieux-être psychologique de la personne. Abstract

Pour un système de santé en français amélioré au Nouveau-Brunswick - Leblanc, Gino (Gouvernement du Nouveau-Brunswick, 2010)

Toward an improved health system in french in New Brunswick - Leblanc, Gino (New-Brunswick Government, 2010)

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, R., Brenda; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

French Language Services, A Factor in the Quality of Healthcare services - Réseau des services de santé en français de l’Est de l’Ontario (2013)
pages: 17

Le Centre de santé de Clare : un modèle pour l'accès à des services de santé en français - Sangaré, Yalla (Reflets, 2014)

Trousse d’accompagnement pour l’examen médical du nouvel arrivant - Sanou, Baroma; Gauthier, Alain; Chomienne, Marie-Hélène; Prud'homme, D.; Kpazaï, G. (2018)
fs-ref-orig: Sanou, B., Gauthier, A., Chomienne, M.-H., Prud'homme, D. et Kpazaï, G. (2018). Trousse d’accompagnement pour l’examen médical du nouvel arrivant. Centre de recherche en santé dans les milieux ruraux et du nord, Institut du Savoir Montfort et Centre de la santé communautaire du Grand Sudbury. fs-code-orig: Sanou-2018

Pratique # 8 : Une infirmière coordonnatrice bilingue en milieu hospitalier à Halifax (IWK Health) (Nouvelle-Écosse) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2019)
À IWK Health, un hopital pédiatrique spécialisé d'Halifax qui offre des services aux familles de l'ensemble des provinces atlantiques, le rôle de l'infirmière coordonnatrice bilingue comporte trois volets : • L’interprétation en français et l’accompagnement des familles francophones ayant besoin de recevoir les informations médicales concernant leur dossier dans leur langue ; • La coordination des dossiers administratifs et de traduction de documents destinés aux usagers francophones ; • Les relations avec la communauté francophone et acadienne. L’infirmière coordonnatrice offre aussi de la formation et du soutien aux employés de l’Hôpital IWK sur l’utilisation des différents systèmes d’interprétation.
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2019, mise à jour 2025). Pratique # 8 : Une infirmière coordonnatrice bilingue en milieu hospitalier à Halifax (IWK Health) (Nouvelle-Écosse). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2025f

Active Offer of French-Language Health Services for Francophone and Acadian Minority Communities in Canada - Joint position statement - Société Santé en français (2017)
pages: 10

L'offre active des services de santé en français dans les communautés francophones et acadienne en situation minoritaire au Canada - Énoncé de position commune - Société Santé en français (2017)
pages: 10